GENERATOR SET MAINTENANCE ANALYSIS IN SIMALUNGUN CITY HOTEL - Saragih, Jopinus; Cui, Zhenyu; Florenta Butar-Butar, Diana; Panjaitan, Hadi (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
The need for electrical energy at Simalungun City Hotel is very high, especially to support all hospitality activities and activities. Therefore, if the electricity goes out, all activities at Simalungun City Hotel will be disrupted. For this reason, it is necessary to have other energy reserves that can replace electricity from PLN when there is a blackout. This energy reserve is obtained from the Generator Set installed at Simalungun City Hotel. In use, the Generator Set (Genset) needs to be maintained and cared for regularly to minimize damage, extend service life and so on. From the results of the research conducted, it was found that the generator set maintenance procedures at Simalungun City Hotel had been properly stated in the Genset maintenance SOP at Simalungun City Hotel. In addition, the level of generator fuel use at Simalungun City Hotel during the study period was 300 liters, where the average hourly use of fuel was 30 liters. So that the level of Genset fuel usage at Simalungun City Hotel is included in the very efficient category when compared to the tables for Genset usage efficiency in general.